FUNGSI PENGAWASAN ORANG ASING OLEH KEIMIGRASIAN DI KANTOR IMIGRASI KELAS I TPI MAKASSAR - Syah Rezah, Farah; Tenri Sapada, Andi; Adha Hamzah, Yuli; Anggraeny Mangarengi, Arianty (Universitas Kapuas, 2024)
There is no doubt that the vast number of foreigners with diverse objectives and interests entering and departing Indonesian territory has an impact on a number of fields. Therefore, one method to deal with the problems caused by the foreign inflow—which, of course, cannot be isolated from immigration violations—is to monitor foreigners in Indonesia. This study demonstrates that, in compliance with Immigration Law Number 6 of 2011, the immigration office at TPI Makassar Class I Immigration Office has been successfully managing foreign nationals. Numerous elements, including those related to legal content, law enforcement, facilities, and infrastructure, have a significant impact on this. cultural and communal aspects. Nonetheless, there are still foreigners accessing Indonesian territory, so the procedure for gathering data on them needs to be enhanced.